Correlation between speaker gender and perceptual quality of mobile speech signal - Al-Othmani, Abdulaleem Z.; Abdul Manaf, Azizah; Zeki, Akram M.; Almaatouk, Qusay; Aborujilah, Abdulaziz; Al-Rashdan, Maen T. (IEEE Xplore, 2020)
Perceptual evaluation of speech signals is a very crucial measure for quality of service in mobile speech communication. Several subjective and objective quality measures are being utilized to evaluate the perceptual quality of speech signals. Perceptual Evaluation of Speech Quality (PESQ)has been found to reliably predict the quality of processed speech signals with a higher correlation with the perceived quality. However, some studied have shown some issues with PESQ measure in specific environments or speech signals. This paper investigates the effect of speaker gender on PESQ measure of the perceptual quality of GSM Full Rate (GSM-FR) encoded speech signals. A Matlab experiment is carried out to encode 350 speech files from TIMIT corpus using GSM-FR vocoder and calculate the PESQ scores. The results clearly show that there is a significant difference in perceptual quality score between female and male speech signals which demonstrate another reliability issue of PESQ as a perceptual quality of speech signal in mobile communications.